SCIENTIFIC AND PRACTICAL CONFERENCE WITH INTERNATIONAL PARTICIPATION «CURRENT ISSUES OF TRAUMA CARE FOR VICTIMS OF TRAFFIC ACCIDENTS» (Неотложная медицинская помощь)
Scientific and practical conference with international participation «Current issues of trauma care for victims of traffic accidents».